Relaps in alcoholics - Mırsal, Hasan; Kalyoncu, Ayhan; Pektaş, Özkan; Şatır, Tulga; Mırsal, Nursel; Beyazyürek, Mansur (Journal of Dependence, 2000)
Alcohol dependence is a chronic disease, often with periods of partial recovery, but it does not always last. After total abstinence, at least 50% of patients may relapse during the first six months. Relapse is well established that drinking after a period of abstinence can lead to a loss of control and a return to the former drinking pattern. Relapse is a process and there are a lot of risk factors. Anger, depression, anxiety are high risk situations. Marital problems, interpersonal conflicts can also lead to relapse. On the other hand pleasant situations such as celebration can also lead to relapse too. Relapse Prevention (RP) is a cognitive-behavioural treatment method. The goal of relapse prevention is to teach individuals who are trying to cope with the problem of relapse. İn tbis article, relapse problem has been revieıved. It has been explained relapseprevention practices in Anatolia Alco-hol Treatment Clinic.
Keywords: Alcohol addiction; depression; wonder; denial